Accounting of Public Institutions - Component of General Accounting and Especially of Public Accounting - Cristina Ioana Antik (Agora International Journal of Economical Sciences (AIJES), 2020)
Public accounting is the accounting that ensures the highlighting of all collection and payment operations related to public funds. It assesses the obligations of taxpayers, highlights the receipts from these obligations and determines the differences from the unfulfilled obligations, as well as the responsibility of the authorizing officers regarding the making of payments from public funds. Its organization is mandatory for all public authorities, territorial communities, national and local public institutions.
Keywords: 330